Digital Radiography Corrosion Mapping on Gas Pipelines - Konar, Radoslav; Mician, Milos; Bucha, Miroslav; Vrzgula, Peter; Hlavaty, Ivo (Communications - Scientific letters of the University of Zilina, 2017)
Digital radiography (DR) is a powerful technique that can be used in non-destructive testing for identification of internal or external defects and corrosion mapping. New generation of digital flat panel detectors become more and more competitive to film detectors, however the transition from film to digital radiography is not always the best choice for every NDT organization especially from the point of view of investments. The paper introduces the application of digital corrosive radiography mapping on gas pipelines using a portable flat panel detector. The experimental part is focused on determining the residual thickness of the pipelines in service.